Smart Shopping System: Integration of Web Technology and IoT for Digital Transformation of Small and Medium-Scale Retail Stores - Banjarnahor, Wiwin Sry Adinda; Sinuraya, Junus; Prayudani, Santi; Tumanggor, Orli (Journal of Computer Science and Informatics Engineering, 2025)
The modern retail sector faces challenges in meeting consumer expectations for efficient and convenient shopping experiences. This research develops a web-based Si-Smart Shop system integrated with Internet of Things (IoT)-based smart shopping cart to optimize retail store operations. The research problem formulation includes reducing customer queue density, providing real-time price information independently, and automating the price label creation process that was previously done manually. The research methodology uses a system development approach with the waterfall model. Implementation results show that the system successfully optimizes operational workflow by reducing consumer waiting time and minimizing price calculation errors. Blackbox testing on 42 test cases demonstrates that all system functionalities meet operational criteria. The main contribution of this research is providing accessible technology solutions for various business scales with affordable investment, addressing operational problems in transaction processes and product information management, as well as improving operational efficiency and service quality in retail environments.